Poland's neighbours are her friends : a drama of non-agression in two acts : text taken from official Polish white book, published 1940.
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Molotov-Ribbentroppact; Wereldoorlog 2; oorlogspropaganda; Polen; Duitsland; Sovjet-Unie.